2022
DOI: 10.1007/s00429-021-02435-0
|View full text |Cite
|
Sign up to set email alerts
|

A hands-on tutorial on network and topological neuroscience

Abstract: The brain is an extraordinarily complex system that facilitates the optimal integration of information from different regions to execute its functions. With the recent advances in technology, researchers can now collect enormous amounts of data from the brain using neuroimaging at different scales and from numerous modalities. With that comes the need for sophisticated tools for analysis. The field of network neuroscience has been trying to tackle these challenges, and graph theory has been one of its essentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 115 publications
0
19
0
Order By: Relevance
“…0-simplexes are nodes, one-simplexes are edges and so on. In figure 2, we illustrated three-and four-simplexes using brain network data from the human connectome project (HCP) project [76,77], as done in [27,73]. Each figure has edge density equal to 0.6% and 1.3%, respectively.…”
Section: Tpts In Functional Brain Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…0-simplexes are nodes, one-simplexes are edges and so on. In figure 2, we illustrated three-and four-simplexes using brain network data from the human connectome project (HCP) project [76,77], as done in [27,73]. Each figure has edge density equal to 0.6% and 1.3%, respectively.…”
Section: Tpts In Functional Brain Networkmentioning
confidence: 99%
“…Each figure has edge density equal to 0.6% and 1.3%, respectively. Data visualization tools were developed in [27,73] and are freely available in [74]. We now move to the study of TPTs in functional brain networks, defined as the loci of the zeros of the EC or the singularity of the Euler entropy.…”
Section: Tpts In Functional Brain Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Higher-order networks are generalized network structures that capture the many-body interaction of complex systems [1][2][3][4][5]. In recent years, they have become increasingly popular to represent different types of data beyond the framework of pairwise interactions, including the human brain [6][7][8][9], social interacting systems [10][11][12][13][14][15][16][17][18], financial networks [19,20], and complex materials [21][22][23]. Interestingly, several studies on synchronization, diffusion, epidemic spreading and evolutionary dynamics have shown that taking into account the higher-order organization of networks can lead to emergent behavior remarkably different from that of graphs, where interactions are limited to groups of two nodes only [24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%